Discovering potential inhibitors against dengue virus NS5 RNA dependent RNA polymerase from local vegetables: a comparative computational study - Md Zahid Hasan; Sheikh Soikot; Md. Motaher Hossain; Maysha Fahmeda Priota; Shanzida Akther; Shianta Jahan; Jahid Bhuyian; Naimur Rahman Sharul; Md. Mosabbir Hossain; Md. Abdulla Al Jubayed; Nilima Rahman; Jannatul Mawya; et al. (Discover Chemistry)
Abstract Dengue virus (DENV) remains a global health challenge, necessitating the identification of novel inhibitors against its NS5 RNA-dependent RNA polymerase (RdRp), a critical enzyme for viral replication. This study evaluates the inhibitory potential of 270 phytochemicals from five local vegetables and computational approaches, with favipiravir as the control. Molecular docking revealed binding energies of -8.8, -8.7, and -8.1 kcal/mol for apigenin-7-glucoside, rutin, and phlorizin, respectively, surpassing favipiravir (-7.4 kcal/mol). These ligands exhibited robust interactions with active site residues, including hydrogen bonds and hydrophobic interactions. Molecular dynamics (MD) simulations over 100 ns confirmed stable protein–ligand complexes, with ligands apigenin-7-glucoside and rutin demonstrating lower Root Mean Square Deviations (RMSD) and favorable Radius of Gyration (Rg) values compared to the control, indicating superior binding stability. Solvent Accessible Surface Area (SASA) and hydrogen bond analyses supported the compactness and interaction strength of apigenin-7-glucoside and rutin. MM/PBSA binding free energy analysis highlighted ligand rutin as the most energetically favorable (-400 to -700 kJ/mol), followed by apigenin-7-glucoside, outperforming favipiravir. Additionally, principal component analysis (PCA) demonstrated distinct ligand-induced conformational effects on NS5 RdRp. The pharmacokinetic evaluations indicated that all three ligands comply with Lipinski’s rule of five, supporting their potential as drug-like candidates. These findings emphasize the potential of vegetable-derived ligands, particularly apigenin-7-glucoside and rutin, as effective inhibitors of DENV NS5 polymerase. Further experimental validation and molecular studies would be required to explore their antiviral applications and potential as alternative therapeutics against dengue.